Custodiol-MP for ex vivo lung perfusion – A comparison in a porcine model of donation after circulatory determination of death. Issue 2 (February 2022) - Kalka, Katharina; Keldenich, Zoe; Carstens, Henning; Walter, Björn; Rauen, Ursula; Ruhparwar, Arjang; Weymann, Alexander; Kamler, Markus; Reiner, Gerald; Koch, Achim
Introduction: Ex vivo lung perfusion (EVLP) is an established technique to evaluate and eventually recondition lungs prior to transplantation. Custodiol-MP (C-MP) solution is a new solution, designed for clinical machine perfusion, that has been used for kidneys. The aim of this study was to compare the effects of EVLP with Custodiol-MP on lung functional outcomes to the gold standard of EVLP with Steen Solution™. Material and Methods: In a porcine EVLP model of DCDD (Donation after Circulatory Determination of Death), lungs were perfused with Steen Solution™ (SS, n = 7) or Custodiol-MP solution supplemented with 55 g/l albumin (C-MP, n = 8). Lungs were stored cold for 4 h in low potassium dextran solution and subsequently perfused ex vivo for 4 h. During EVLP pulmonary gas exchange, activities of lactate dehydrogenase (LDH) and alkaline phosphatase (AP) as well as levels of lactate in the perfusate were recorded hourly. Results: Oxygenation capacity differed significantly between groups (averaged over 4 h: SS 274 ± 178 mmHg; C-MP 284 ± 151 mmHg p = 0.025). Lactate dehydrogenase activities and lactate concentrations were significantly lower in Custodiol-MP perfused lungs. In a porcine model of DCDD with 4 h of EVLP the use of modified Custodiol-MP as perfusion solution was feasible. The use of C-MP showed at least comparable lung functional outcomes to the use of Steen Solution TM . Furthermore C-MP perfusion resulted in significantly lower lactate dehydrogenase activity and lactate levels in the perfusate and higher oxygenation capacity.